PENGARUH KINERJA PAKET WISATA UMRAH DAN HAJI KHUSUS TERHADAP RETENSI PELANGGAN PT. AMANAH MULIA WISATA (AMWA TOURS) SEBAGAI TRAVEL PENYELENGGARA UMRAH DAN HAJI KHUSUS DI KOTA BANDUNG : Survei Terhadap Alumni Jemaah Umrah dan Haji Khusus Amwa Tours Tahun 2008 di Kota Bandung - Cici Sulastri, - (2010)
Religious tourism is one type of tourism activities which include various holy sites (holy place) and pilgrimage sites which aims to make a trip to meet the spiritual desire for someone to be closer to its creator. One form of tourist pilgrimage in Islam is the Hajj and Umrah. In 2008 and 2009, there were approximately three million people who perform the Hajj trip around eight to ten million people worship Umrah from all over the world every year. PT. Amanah Mulia Wisata or known by the AMWA Tours is one of the umrah and hajj travel company specialized in the city of Bandung. AMWA Tours's number of pilgrims who feel less comfortable with some of the facilities offered by AMWA Tours's packages in 2008, negatively impact the overall packages, so that the pilgrims who had used the package in 2008, do not re-purchase (retention) of the package from AMWA Tours in the following year, nor will recommend the package to others, so a decline in customer retention in 2009. Based on the description above, so we conducted research on the performance of tour packages to AMWA Tours's customer retention in Bandung. This research was carried out to alumni of Umrah and Hajj pilgrims specially AMWA Tours in 2008. The purpose of this study to find out the performance tours packages, customer retention in AMWA Tours and influence the performance of tour packages to AMWA Tours's customer retention. The method used in this research is descriptive and verification using multiple linear regression analysis. The results of this study indicate that the performance of a tour packages to have an assessment of the respondents are good with AMWA Tours's customer retention high enough. The results indicate that there is significant influence between the performance of tour packages to customer retention. The calculation result obtained Fcount 39.910 while Ftable with degrees of freedom 100 at α (0.05) is of 3.09. It is directed that the performance of tour packages affect customer retention. The value of determination coefficient of 0.752. This indicates that 75.2% customer retention is influenced by the performance of AMWA Tours's travel packages while the remaining 24.8% is for other factors that affect customer retention in AMWA Tours.